New characterization of the class of starlike functions - Owa, Shigeyoshi; YAVUZ, EMEL; POLATOĞLU, YAŞAR (The Korean Mathematical Society, 2008)
For analytic functions f(z) in the open unit disc D, an operator Nα(f(z)) relating with starlike functions is introduced. The object of the present paper is to discuss some properties of the operator Nα(f(z)).
Keywords: Caratheodory function; starlike function; operator